Cisco CCIE Fundamentals: Network Design & Case Studies - McGregor, Mark (Cisco Press, 2011)
Part 1: Internetwork Design provides a set of general guidelines for planning internetworks and specific suggestions for several key internetworking implementations. Part 1 focuses on identifying the essential technologies and appropriate implementations for specific environments. Part 2: Internetworking Case Studies provides practical examples illustrating how readers can implement Cisco Systems software features. Case studies address implementation concerns and show how to apply features. Detailed configuration file examples and network diagrams are included.